A novel approach to explain the inactivation mechanism of Escherichia coli employing a commercially available peracetic acid - Flores, Marina J (Water science and technology : a journal of the International Association on Water Pollution Research, 2014)
The chemical inactivation of Escherichia coli employing a commercial mixture of peracetic acid (PAA) was studied. For this purpose, experiments were carried out using dilutions of the unmodified mixture, and also the same mixture but altered with hydrogen peroxide (HP) previously inhibited. Also, these results were compared to those obtained before employing HP alone. It was found that the mixture is much more efficient than HP and PAA acting separately. Furthermore, it was found that PAA without HP is much more efficient than HP alone. A plausible explanation is presented. The homolysis of PAA would give rise to a chain reaction that generates a significant number of highly oxidizing radicals. An attacking scheme to bacteria in two stages is proposed, where the initial step, mainly caused by PAA, is very fast and eliminates some specific components of the bacteria that would otherwise inhibit the parallel action of HP. Thereafter, the emergence of a potentiating synergetic action of the second oxidant seems to be immediately unveiled